Vibration measurement without the Heydemann correction. (December 2021) - Kokuyama, Wataru; Shimoda, Tomofumi; Nozato, Hideaki
Abstract: We propose a novel signal-processing technique to avoid cyclic errors in laser interferometers instead of an elliptical fitting, known as the Heydemann correction. It is based on a simple superposition of background motions to average out the effect of cyclic errors. With a simulation, we show that a single-frequency vibration can be extracted by applying filtering and fitting to the displacement data with an adding linear drift. We also experimentally show that the technique reduces the measured dispersion of the vibration amplitude. It offers a simple and economic interferometer for the single-frequency vibration measurement in primary vibration calibration systems.